2020
DOI: 10.4054/demres.2020.42.29
|View full text |Cite
|
Sign up to set email alerts
|

Entrance into parenthood at the onset of low fertility in Ukraine: The role of family relationships and perceived security

Abstract: BACKGROUND In post-Soviet countries, low fertility has been achieved through postponement of second birth, while entrance into parenthood still takes place relatively early in life and within marriage. Studies suggest that grandparental support with childcare drives this reproductive behaviour. However, we still know little about the exact way in which decisions about first parenthood are shaped by family relationships, especially with respect to the expected and actual support they exert. OBJECTIVE This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The Influence of Kin Proximity on Reproductive Success of choice. Qualitative evi dence from the twen ti eth cen tury sug gests that as cou ples become more aware of the costs of childrearing, they make more planned choices about their fer til ity and who will pro vide sup port for rais ing chil dren (Hilevych 2018(Hilevych , 2020Hilevych and Rusterholz 2018;Rusterholz 2015). If G1 and G2 cou ples were mak ing ratio nal deci sions about migra tion and where they would live in rela tion to each other, it is likely that G2 child bear ing cou ples became increas ingly cog ni zant of the poten tial role of kin in car ing for young G3 chil dren.…”
Section: Corrected Proofsmentioning
confidence: 99%
“…The Influence of Kin Proximity on Reproductive Success of choice. Qualitative evi dence from the twen ti eth cen tury sug gests that as cou ples become more aware of the costs of childrearing, they make more planned choices about their fer til ity and who will pro vide sup port for rais ing chil dren (Hilevych 2018(Hilevych , 2020Hilevych and Rusterholz 2018;Rusterholz 2015). If G1 and G2 cou ples were mak ing ratio nal deci sions about migra tion and where they would live in rela tion to each other, it is likely that G2 child bear ing cou ples became increas ingly cog ni zant of the poten tial role of kin in car ing for young G3 chil dren.…”
Section: Corrected Proofsmentioning
confidence: 99%
“…The involvement of parents (in-law), especially mothers (in-law), reinforced men being seen as mere 'helpers', rather than equals in infant care. As shown elsewhere (Hilevych, 2020), help from parents (in-law) was crucial to the early stages of marriage and childcare. Receiving help was often possible through, even temporary, co-residence arrangements:…”
Section: Finding a Father's 'Niche' In Women-oriented Childcare Arran...mentioning
confidence: 83%
“…The original study focused on regional urban variations in fertility decline and family relations in Soviet Ukraine (Hilevych, 2016b). As I elaborate elsewhere, there were some regional differences in grandparents' -mostly grandmothers' -involvement and how women perceived the role of men in these two urban contexts (Hilevych, 2020(Hilevych, , 2016a. Extending this analysis in the following, I explore men's welfare through the lens of their involvement in childcare and from their own perspectives.…”
Section: Methodsmentioning
confidence: 99%
“…For example, one study reported that the population in eastern and southern Ukraine declined by 28% between 195128% between and 198728% between (Pallot, 1990. Similarly, for urban areas in eastern Ukraine, the emergence of low fertility has been traced to the postwar period (Hilevych, 2016(Hilevych, , 2020. to fewer second and higher order births (Perelli-Harris, 2005).…”
Section: Depopulation In Ukrainementioning
confidence: 99%